Stakeholder Synergy Analysis in the Reksa Village Program in Sleman Regency - Mukminin, Fuad Khoiril; Retnandari, Nunuk Dwi (International Journal Labs, 2024)
Social change in all fields can have the potential for social conflicts. The diverse conditions of Sleman Regency certainly have a very positive influence on the acceleration of development in Sleman Regency The potential for social conflicts must be managed properly through the Village Mutual Program (Village Movement for Early Detection and Prevention towards Safe Villages). This movement is based on the independence of community members together with the village government to create immunity in their environment from all forms of problems that have the potential for social conflicts. The purpose of this study is to analyze the level of synergy of stakeholders in the Village Mutual Program in Sleman Regency. This research uses a descriptive qualitative method. The results of this study show that the synergy between stakeholders in the Village Mutual Program is found in 5 (five) indicators (communication network structure, reciprocal/response relationships, standard measures and activity procedures, cooperation/coordination and trust between parties) which are tested on 4 (four) stakeholders obtained an average score of 75%, meaning that the level of stakeholder synergy in the Village Mutual Program in Sleman Regency is already good.